cDNA cloning and functional expression of the Schistosoma mansoni protective antigen triose-phosphate isomerase. - Shoemaker, C (1992)
M.1 monoclonal antibody has previously been shown to passively transfer partial resistance to schistosome infection within mice and to recognize a 28-kDa antigen that has peptide sequence homology with triose-phosphate isomerase (TPI; D-glyceraldehyde-3-phosphate ketol-isomerase, EC 5.3.1.1). We have now isolated the complete coding DNA for Schistosoma mansoni TPI and confirmed that this cDNA encodes the 28-kDa antigen recognized by M.1. The predicted translation product has strong homology with other TPIs, particularly from higher eukaryotes, and the sequence homology is greatest in regions known to form the active site. The complete coding DNA has been expressed within an Escherichia coli host to produce high levels of soluble, recombinant S. mansoni TPI protein. The product is recognized and purified by the M.1 antibody and is a functional TPI with an intrinsic specific activity comparable to that of rabbit and yeast TPI.